1991
DOI: 10.1080/15287399109531527
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human fetal brain acetylcholinesterase: Marker effect of neurotoxicity

Abstract: Human fetal brains were obtained after medical termination of pregnancy at 8-10 wk from informed patients. A definite regionalization of AChE was found in the brain of the fetus, with cerebellum recording the highest and cerebral hemisphere the lowest activity. Optimum conditions for the cerebellar AChE activity were determined with respect to molarity of the buffer, pH, temperature, and concentrations of substrate (acetylthiocholine iodide), activators (NaCl, MgCl2), and thiol indicator (dithiobisnitrobenzoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…While chronic diazepam treatment at 30 mg/kg/day caused only a slight but non significant increase in both plasma and RBC enzyme activity which was about 9% and 13% respectively of the control group . Estimation of acetyl cholinesterase activity is of importance in studies concerning enzyme synthesis mechanisms (10)(11)(12). In the present study, we found that long-term administration of chlorpromazine increased blood Ache activity.…”
Section: Resultssupporting
confidence: 62%
“…While chronic diazepam treatment at 30 mg/kg/day caused only a slight but non significant increase in both plasma and RBC enzyme activity which was about 9% and 13% respectively of the control group . Estimation of acetyl cholinesterase activity is of importance in studies concerning enzyme synthesis mechanisms (10)(11)(12). In the present study, we found that long-term administration of chlorpromazine increased blood Ache activity.…”
Section: Resultssupporting
confidence: 62%
“…All four children also suffered from mental and growth retardation. Maternal exposure to organophosphates is likely to affect the acetylcholinesterase present in fetal brains as well as the fetal neural function (68). Organophosphate exposure in fetuses, neonates, and infants is an area of developmental toxicology that requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Acetyl cholinesterase (AChE) is a membrane bound enzyme found in different tissues and play a important role for regulation of most physiological event, involving the turnover of acetylcholine (1)(2)(3). The activity of blood and/or 'true' AChE have been found to be affected by a number of antipsychotic drugs (1,(4)(5)(6)(7)(8)(9).Chronic treatment of rat and/or chicks with chlorpromazine and diazepam resulted increase in AChE activity (4,5). Similar finding were obtained from enzyme assay of chick and rabbit brain and cerebrospinal fluid (10).The effect by chlorpromazine in true AChE activity appear to be reversible (1), depending on the duration of drug administration (11).…”
Section: Introductionmentioning
confidence: 99%